2016
DOI: 10.1371/journal.pone.0153488
|View full text |Cite
|
Sign up to set email alerts
|

Transfer RNA Bound to MnmH Protein Is Enriched with Geranylated tRNA – A Possible Intermediate in Its Selenation?

Abstract: The wobble nucleoside 5-methylaminomethyl-2-thio-uridine (mnm5s2U) is present in bacterial tRNAs specific for Lys and Glu and 5-carboxymethylaminomethyl-2-thio-uridine (cmnm5s2U) in tRNA specific for Gln. The sulfur of (c)mnm5s2U may be exchanged by selenium (Se)–a reaction catalyzed by the selenophosphate-dependent tRNA 2-selenouridine synthase encoded by the mnmH (ybbB, selU, sufY) gene. The MnmH protein has a rhodanese domain containing one catalytic Cys (C97) and a P-loop domain containing a Walker A motif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 41 publications
(89 reference statements)
0
57
1
Order By: Relevance
“…As expected, we found that a single geranyl modification increases the hydrophobicity of the geS2U–RNA strand in comparison to the reference U (ΔLog P = 0.27) and S (ΔLog P = 0.10) RNA strands (Table 2). Although it has been suggested that the presence of a hydrophobic geranyl residue in the tRNAs affects their intracellular localization and transport through the cell membranes (11,15), recent studies have shown a lack of geranylated tRNA enrichment in outer or inner cellular membranes (9). …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As expected, we found that a single geranyl modification increases the hydrophobicity of the geS2U–RNA strand in comparison to the reference U (ΔLog P = 0.27) and S (ΔLog P = 0.10) RNA strands (Table 2). Although it has been suggested that the presence of a hydrophobic geranyl residue in the tRNAs affects their intracellular localization and transport through the cell membranes (11,15), recent studies have shown a lack of geranylated tRNA enrichment in outer or inner cellular membranes (9). …”
Section: Discussionmentioning
confidence: 99%
“…In earlier studies, we chemically transformed S2U to Se2U via S -geranyl-2-thiouridine and suggested a possible linear mechanism for the SelU-catalyzed reaction, in which geS2U exists as an intermediate in the cellular transformation of S2U to Se2U (Figure 5) (14). Such a possibility has been recently considered in advanced studies on tRNA selenouridine synthase (9). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations